Hydrogen production on Ni loaded apatite-like oxide synthesized by dissolution-precipitation of natural phosphate. (27th July 2017) - Mesrar, Farah; Kacimi, Mohamed; Liotta, Leonarda F.; Puleo, Fabrizio; Ziyad, Mahfoud
Abstract: A calcium phosphate oxide with composition analogous to the apatite phosphate, was synthesized by dissolution and precipitation of Moroccan natural phosphate, then, used as a carrier for deposition of different amount of nickel (2.5, 5, 10 wt%). The so obtained support and the resulting catalysts were characterized by several techniques, such as ICP-AES, XRD, BET, FT-IR, DRS, TPR. XRD characterization showed that the support has the crystalline structure typical of apatite and the chemical composition was close to that of fluoroapatite with some fluoride partially substituted by hydroxide ions. After impregnation of Ni, a portion of Ca 2+ ions of the support was exchanged by Ni 2+ ions, as confirmed by UV–visible–NIR analysis. The prepared catalysts were tested in the methane dry reforming reaction without performing any reduction pre-treatment except the exposure to the reaction mixture. High catalytic activity at 700 °C and good stability in the production of hydrogen were registered for such Ni loaded samples suggesting a good resistance to coke poisoning according to the basic nature of the support. Graphical abstract: Highlights: Dissolution and precipitation of Moroccan natural phosphate as raw material. Synthesis of Ni catalysts over the apatite-like oxide. Ni 2+ ions partially exchanged with Ca 2+ coexist with NiO particles at high contents. Effect of Ni loading, 2.5, 5, 10 wt% on dry reforming of methane. High catalytic activity in CH4 and CO2 conversion at 700 °C and stable H2 production.